Marx’s Thoughts on Human Essence and Its Realistic Significance from the Perspective of Artificial Intelligence - Youqiang Wang; Xuan Kang; Jiayue Xiong (Computer Sciences & Mathematics Forum)
The evolution of Marx’s ideation was accompanied by a continuous, in-depth understanding of human essence. From the promotion of human self-consciousness to the status of divinity to the transformation of humans into a human essence, his thoughts turned from idealism to humanistic material. Subsequently, from the fact that a human is the embodiment of human essence to the fact that man is the sum of all social relationships, Marx finally turned to practical materialism. Marx’s thoughts on human essence illustrated the beautiful development of mankind and the assumption of personal, happy life. He uncovered the beauty of human nature, labor, harmony, and practice in human essence and pursued the return of human essence to “beauty” throughout his life. In the contemporary era, with the popularization of artificial intelligence, the development of the machine industry in the 19th century precipitated problems similar to those faced today regarding unemployment and how human development has caused machines to replace people due to today’s popularization of intelligence. Today, Marx’s thoughts on human essence still offer insights and hold practical significance.